Analisis Peran Komunikasi Organisasi dalam Meningkatkan Efektivitas Tim Pengelola Pendidikan Di Sekolah SMP Swasta Islam Terpadu Suhairiyah - Tarisa Munawwarah; Nur Alfiana Kholizah; Maidiana M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
One aspect that really determines the success of educational management is the importance of establishing effective communication between educational institution staff. Communication plays a crucial role in social interaction, which in turn influences the atmosphere of activities. Activities, as part of the social structure, are the main focus in developing communication characteristics in order to optimize activities. The use of linguistic and nonverbal communication has a significant impact on the conditions of activity, reflects the vision and mission of the organization. In an indirect way, effective communication is an important key in advancing an institution. In this context, the research aims to analyze the role of organizational communication in increasing the effectiveness of education management teams. The method used is a literature study, where the author examines various sources relevant to the topic. The conclusion of this research shows that organizational communication is a critical factor that needs serious attention from the education management team in order to increase their effectiveness.